1992
DOI: 10.1111/j.1439-0264.1992.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Nerve Root Origins of the Cutaneous Nerves of the Feline Pelvic Limb

Abstract: The dorsal root origins of cutaneous nerves supplying the feline pelvic limb were determined electrophysiologically in 11 cats. Cutaneous nerves were surgically exposed and the presence or absence of an evoked potential in response to stimulation of individual dorsal roots was noted. The dorsal cutaneous branches of L3-L5 and S3, and the lateral cutaneous branch of L3 each arose solely from their parent spinal nerves. The L7, S1, and S2 dorsal cutaneous branches had multiple dorsal root origins. The lateral cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
2
19
1
6
Order By: Relevance
“…However, in our study and indirectly in Bayley's description, the cutaneus femoris lateralis was observed as a branch of the first trunk, similarly to described in South American fur seal (Castro et al, 2009). Still, the nerve genitofemoralis was not formed by the LSP or by the first trunk as described in dogs (Fletcher, 1970, Bailey et al, 1988, but was originated from L3-4. No differences were observed in structures innervated by the femoralis and obturatorius in dogs, P. gymnocercus and C. thous, but our results showed three branches emerging from the femoralis: two rami innervating the femoral medial muscles, while the nerve saphenus (third ramus) supplying the medial musculature and skin of the limb distal portion.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…However, in our study and indirectly in Bayley's description, the cutaneus femoris lateralis was observed as a branch of the first trunk, similarly to described in South American fur seal (Castro et al, 2009). Still, the nerve genitofemoralis was not formed by the LSP or by the first trunk as described in dogs (Fletcher, 1970, Bailey et al, 1988, but was originated from L3-4. No differences were observed in structures innervated by the femoralis and obturatorius in dogs, P. gymnocercus and C. thous, but our results showed three branches emerging from the femoralis: two rami innervating the femoral medial muscles, while the nerve saphenus (third ramus) supplying the medial musculature and skin of the limb distal portion.…”
Section: Discussionmentioning
confidence: 82%
“…However, was not prefixed type because L3 and L4 ventral branches not form the plexus, but was post-fixed due participation of S1-2 ventral branches. More, the plexus presented three trunks: L5-6-S1, L6-7-S1-2 and L7-S1-2, while in dog were described two (L3-6 and L6-7-S1-2, Fletcher, 1970;Bailey et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations